IMPACT OF BARNEY AND FRIENDS PROGRAMME ON COGNITIVE DEVELOPMENT AMONG EARLY CHILDHOOD - Razali, Noorma; Bullare @ Bahari, Ferlis; T.G, Rejani (Journal of Human Capital Development (JHCD), 2014)
Television is a world full of images. Various programmes are designed specifically for children whether it is educational programme or not, and these programmes are keeping pace with the development around the world. Children at early childhood phase are normally interested in television programme that give them entertainment and joyful. Educational pogrammes like Barney and Friends, is an example of the fovourite television programme amongst the children of this age group. The purpose of the study was to examine the impact of Barney and Friends programme on cognitive development among children at early childhood. A total of 40 children aged between 24 months and 42 months were selected from several kindergartens around Indah Permai residential area, Kota Kinabalu, Sabah. This research employed experimental design within and between subjects with pre and posttest group design. In this study, the children were allowed to watch two series of Barney and friends programme. Data were measured using the Bayley Scales of Infants Development (BSID-II). Results showed that the Barney and Friends programme had a significant impact on the cognitive development of children at early childhood. Keywords: aeducational television programme, cognitive development, early childhood